Development of Allosteric Modulators of Voltage-Gated Na+ Channels: A Novel Approach for an Old Target - Dvorak, Nolan M.; Wadsworth, Paul A.; Wang, Pingyuan; Zhou, Jia; Laezza, Fernanda (Current Topics in Medicinal Chemistry, 2021)
Given their primacy in governing the action potential (AP) of excitable cells, voltage-gated Na+ (Nav) channels are important pharmacological targets of therapeutics for a diverse array of clinical indications. Despite historically being a traditional drug target, therapeutics targeting Nav channels lack isoform selectivity, giving rise to off-target side effects. To develop isoform-selective modulators of Nav channels with improved target-specificity, the identification and pharmacological targeting of allosteric sites that display structural divergence among Nav channel isoforms represents an attractive approach. Despite the high homology among Nav channel α subunit isoforms (Nav1.1-Nav1.9), there is considerable amino acid sequence divergence among their constituent C-terminal domains (CTD), which enables structurally and functionally specific protein: protein interactions (PPI) with auxiliary proteins. Although pharmacological targeting of such PPI interfaces between the CTDs of Nav channels and auxiliary proteins represents an innovate approach for developing isoform-selective modulators of Nav channels, appreciable modulation of PPIs using small molecules has conventionally been difficult to achieve. After briefly discussing the challenges of modulating PPIs using small molecules, this current frontier review that follows subsequently expounds on approaches for circumventing such difficulties in the context of developing small molecule modulators of PPIs between transmembrane ion channels and their auxiliary proteins. In addition to broadly discussing such approaches, the implementation of such approaches is specifically discussed in the context of developing small molecule modulators between the CTD of Nav channels and auxiliary proteins. Developing allosteric modulators of ion channels by targeting their PPI interfaces with auxiliary proteins represents an innovative and promising strategy in ion channel drug discovery that could expand the “druggable genome” and usher in first-in-class PPI-targeting therapeutics for a multitude of channelopathies.
Keywords: Drug discovery